Inter-layer thermal contact resistance evolution with the degree of intimate contact in the processing of thermoplastic composite laminates. (February 2014) - Levy, Arthur; Heider, Dirk; Tierney, John; Gillespie, John W
This article focuses on the contact between layers in forming processes of composite laminate. The link between the degree of intimate contact and the consequent thermal contact resistance between layers is investigated. A hot plate forming process experiment allows to propose a relation and determine the missing parameter for APC2 thermoplastic prepreg composite. Besides the new proposed relation, this work showed that the internal thermal contact resistances in the laminate is significant. Therefore, thermal modeling of forming processes of composite laminate (such as automatic tape placement) should account for this phenomenon.